Radioimmunotherapy of B-Cell Non-Hodgkin’s Lymphoma - Bodet-Milin, Caroline; Ferrer, Ludovic; Pallardy, Amandine; Eugène, Thomas; Rauscher, Aurore; Faivre-Chauvet, Alain; Barbet, Jacques; Kraeber-Bodéré, Françoise (Frontiers in Oncology, 2013)
This manuscript reviews current advances in the use of radioimmunotherapy (RIT) for the treatment of B-cell non-Hodgkin’s lymphoma (NHL). RIT has been in use for more than 20 years and has progressed significantly with the discovery of new molecular targets, the development of new stable chelates, the humanization of monoclonal antibodies (MAbs), and the use of pretargeting techniques. Today, two products targeting the CD20 antigen are approved: 131I-tositumomab, (Bexxar®) and 90Y-ibritumomab tiuxetan, (Zevalin®). 131I-tositumomab is available in the United States, and 90Y-ibritumumab tiuxetan in Europe, the United States, Asia, and Africa. RIT can be integrated in clinical practice using non-ablative activities for treatment of patients with relapsed or refractory follicular lymphoma (FL) or as consolidation after induction chemotherapy in front-line treatment in FL patients. Despite the lack of phase III studies to clearly define the efficacy of RIT in the management of B lymphoma in the era of rituximab-based therapy, RIT efficacy in NHL has been demonstrated. In relapsing refractory FL and transformed NHL, RIT as a monotherapy induces around 30% complete response with a possibility of durable remissions. RIT consolidation after induction therapy significantly improves the quality of the response. Dose-limiting toxicity of RIT is hematological, depending on bone marrow involvement and prior treatment. Non-hematological toxicity is generally low. Different studies have been published assessing innovative protocols of RIT or new indications, in particular treatment in patients with aggressive lymphomas. High-dose treatment, RIT as consolidation after different therapeutic induction modalities, RIT in first-line treatment or fractionated RIT showed promising results. New MAbs, in particular humanized MAbs, or combinations of naked and radiolabeled MAbs, also appear promising. Personalized dosimetry protocols should be developed to determine injected activity.